Novel Compact CPW-Fed Antennas with Harmonic Suppression and Bandwidth Enhancement. (27th August 2012) - Zhou, Zhi-Li; Li, Li; Hong, Jing-Song
Abstract : Novel compact CPW-fed antennas with harmonic suppression are presented and investigated in detail. By inserting symmetrical slots connected to the end of CPW transmission line in the ground plane, and exploiting parasitic technique, harmonic suppression, compact size, as well as wide bandwidth are obtained. General performances of the proposed antennas are studied by equivalent transmission line circuits. Moreover, the steps of constructing such harmonic suppression antennas are derived. Eventually, the experiment results verified the validation of the proposed harmonic suppression antennas.